Optimalisasi Pemasaran Melalui Digitalisasi Pada Produk UMKM Seblak Cik Maya di Kota Bengkulu - Pratiwi, Anggun; Febliansa, Muhammad Rahman; Soleh, Ahmad (Jurnal Dehasen Untuk Negeri, 2025)
Small-scale local entrepreneurs are often the pulse of the grassroots economy that supports the pulse of daily life. Seblak Cik Maya is one of the local businesses that is growing in Bengkulu City and is engaged in the culinary specialty. In the midst of the digital era that continues to develop, traditional strategies are starting to be abandoned and shifting towards a digital-based system. This study aims to optimize the digital marketing strategy that can be implemented by Seblak Cik Maya in order to reach a wider market and increase sales. The method used is descriptive qualitative through direct observation, interviews with business owners, and documentation of marketing activities that have been carried out. The results show that with the right digital approach, Seblak Cik Maya has the potential to increase brand visibility and expand customer reach. This study provides a contribution in the form of understanding and technical assistance regarding digital marketing based on social media for local entrepreneurs. In addition, this study also provides implementation recommendations that can be used as a reference by similar MSMEs in adapting digitalization as a sustainable means in the current era of digital transformation.